Visean terrigenous sediments of the South Tatar Arch (Volga-Urals oil and gas bearing province) – multifacial filling of the karst surface of the Tournaisian isolated carbonate platform - V. V. Silantiev; M. F. Validov; D. N. Miftakhutdinova; N. G. Nourgalieva; E. A. Korolev; B. G. Ganiev; A. A. Lutfullin; K. D. Shumatbaev; R. M. Khabipov; V. A. Sudakov; Yu. A. Akhmadullina; K. A. Golod; et al. (Georesursy)
The paper presents new thickness and sandiness maps of the Visean terrigenous strata (Radayevkian and Bobrikian regional stages, Lower Carboniferous) of the South Tatar Arch, constructed using the “Natural Neighbour” spatial interpolation method in ArcGIS Pro software based on the analysis of geophysical survey data for more than 30,000 boreholes.The interpretation of the maps in combination with the results of sedimentological, ichnotextural and petrophysical core studies, supplemented by the analysis of archival and published materials, provided an opportunity to update the approach to modelling the sedimentation of the terrigenous Lower Carboniferous of the South Tatar Arch. The proposed sedimentation models of terrigenous and coal-bearing sediments take into account the chronostratigraphic data, the karstification of isolated carbonate platforms, the sediment accumulation rates and the ichnotextural characteristics of the sediments. It is concluded that the accumulation and preservation of terrigenous and peat (coal-bearing) sediments differ in duration (0.1 million years vs. 1.5–2 million years) and are consequently associated with transgressive and regressive phases.The accumulation of terrigenous sediments includes: (a) transgressive eustatic episodes – short-term incursions of a marine basin onto the eroded surface of an isolated carbonate platform, during which silty and sandy, wellsorted bioturbated sediments were accumulated, often with a variety of ichnofossils of marine benthic organisms; (b) the regressive eustatic phase resulted in the predominant erosion of sediments on the arch; whereas sediments in the incisions were largely preserved.The accumulation of peat (coal-bearing) deposits includes (a) the regressive eustatic phase, during which the vast area of the eastern Volga-Urals region was covered with flourishing vegetation and stable swamp environments were forming in the incisions of the Tournaisian surface; (b) the transgressive phase – the peat was overlaid and buried by transgressive marine silt-sand sediments; then it was compacted and transformed into coal. The alternation of coal-bearing and transgressive intervals indicates the cyclicity of these processes.The proposed sedimentation models extend the concepts of previous studies and are consistent with the developed maps of thickness and sandiness of the Lower Carboniferous terrigenous sediments, explaining the complex, covering and mosaic distribution of sand bodies over the area, as well as the filling of incisions with sediments of different lithological types.